2‐Bromo‐6‐[18F]fluoropyridine: two‐step fluorine‐18 radiolabelling via transition metal‐mediated chemistry†. (18th December 2013) - Betts, Helen M.; Robins, Edward G.; Dilworth, Jonathan R.; Pascu, Sofia I.
<x xml:space="preserve">Abstract</x> Novel radiolabelling methods are important for the development of new tracers for positron emission tomography. Direct nucleophilic fluorination of aromatic rings with [18F]fluoride is limited to activated substrates, restricting the application of this approach. Inspired by transition metal‐mediated transformations, a fluorine‐18 synthon was prepared to supplement the radiolabelling methods available for molecules unsuitable for direct labelling. 2‐Bromo‐6‐[18F]fluoropyridine (denoted [18F]1) was prepared in high yield, and palladium‐mediated cross‐coupling reactions were exemplified. High incorporation of fluoride and efficient cross‐coupling reactions demonstrate that compound [18F]1 holds promise as a new synthon for construction of fluorine‐18‐labelled molecules via transition metal‐mediated reactions.